Genetic Alterations in Essential Thrombocythemia Progression to Acute Myeloid Leukemia: A Case Series and Review of the Literature - Ayres-Silva, Jackline P.; Bonamino, Martin H.; Gouveia, Maria E.; Monte-Mor, Barbara C. R.; Coutinho, Diego F.; Daumas, Adelmo H.; Solza, Cristiana; Braggio, Esteban; Zalcberg, Ilana Renault (Frontiers in Oncology, 2018)
The genetic events associated with transformation of Myeloproliferative Neoplasms (MPN) to secondary Acute Myeloid Leukemia (sAML), particularly in the subgroup of Essential Thrombocythemia (ET) patients, remain incompletely understood. Deep studies using high-throughput methods might lead to a better understanding of genetic landscape of ET patients who transformed to sAML. We performed array-based comparative genomic hybridization (aCGH) and whole exome sequencing (WES) to analyze paired samples from ET and sAML phases. We analyzed five patients with previous history of MPN. Four had initial diagnosis of ET (one case harboring JAK2 p.Val617Phe and the remaining three CALR type II p.Lys385fs*47), and one was diagnosed with MPN/myelodysplastic syndrome with thrombocytosis (SF3B1 p.Lys700Glu). All were homogeneously treated with hydroxyurea, but subsequently transformed to sAML (mean time of 6 years/ median of 4 years to transformation). Two of them have chromosomal abnormalities and both acquire 2p gain and 5q deletion at sAML stage. The molecular mechanisms associated to leukemic progression in MPN patients are not clear. Our WES data showed TP53 alterations recurrently observed as mutations (missense and frameshift) and monoallelic loss. On the other hand, aCGH showed novel chromosome abnormalities (+2p and del5q) potentially associated with disease progression. The results reported here add valuable information to the still fragmented molecular basis of ET to sAML evolution. Further studies are necessary to identify minimal deleted/amplified region and genes relevant to sAML transformation.